AB0610 Value of Ultrasonography Parotid Glands in Patients with Suspected Primary Sjögren's Syndrome. (9th June 2015) - Scarafia, S.O.; Oliver, M.; Gonzalez, P.; Vila, D.; Santiago, L.; Fernandez Nacul, S.; Secco, A.; Mamani, M.
Abstract : Background: Primary Sjögren's syndrome (pSS) is an autoimmune disease, which affects the exocrine glands. The most serious complication is development lymphomas, having a close relationship with the presence of hypocomplementemia, cryoglobulins, parotid swelling and a Minor Salivary Gland Biopsy (MSGB) with III or IV score (Chisholm and Mason Classification). Therefore the evaluation of the salivary glands have both diagnostic and prognostic value in pSS. The MSGB is a minimally invasive procedure, though not without complications. The parotid ultrasonography (US) is a noninvasive, economic, imaging tool, that has been demonstrated to be useful in the diagnosis of patients with suspected pSS. Recent studies that evaluated its utility to replace the Sialography on American-European Criteria or as an additional item in the 2012 American College of Rheumatology Classification Criteria. Objectives: Assess the diagnostic value of ultrasonography (US) in those patients underwent minor salivary gland biopsy (MSGB) by suspected Primary Sjögren Syndrome (pSS). Methods: All patients underwent bilateral parotid glands US and MSGB. The same expert blinded examiner performed the US. All patients were scanned using an MyLab 25 US scanner (Esaote Italy) with a 10-18 MHz linear-array transducer. The following parameters were assessed: homogeneity, hypoechoic areas, hyperechoic foci, Power Doppler (PD) and margins graded from 0 to 2 (0: well-defined, 1: ill-defined, 2: blurred) and gland size was measured. The gold standard was the MSGB. According to the quantity and type of US variables, we determined the following cut-off values (at least unilateral parotid finding) A: presence of heterogeneity on unilateral or bilateral parotid glands B: presence of any variable (not more than one and excluding heterogeneity) on unilateral or bilateral parotid glands. C: presence of three or more variables (any variable) on unilateral or bilateral parotid glands. Results: We included a total of fifty-one biopsies (36 negative and 15 positive). 96.1% were female. According to A cut-off values had 47% sensitivity (S) (CI 33-60), 69% specificity (Sp) (CI 57-82), 39% positive predictive value (PPV) (26-52), 77% Negative Predictive Value (NPV) (CI 64-88) and Positive Likelihood Ratio (LR+) 1.5 (CI 0.7-3.2). B findings showed 33% S (CI 20-46), 86% Sp (CI 77-96), 50% PPV (CI 36-64), 76% NPV (CI 64-87%) amd LR+ 2.4 (CI 0.8-7.1). We observed C findings with a 33% of Sensitivity (CI 20-46), 75% Specificity (CI 63-87), 36% PPV (CI 23-49), 73% NVP (CI 61-85) and LR+ 1.6 (CI 0.7-3.7). Conclusions: We considered that B findings are the best cut-off values because it demonstrated greater specificity. Nevertheless, in our study the US of parotid gland not prove to be an appropriate diagnostic tool to replace the MSGB. References: Takagi Y, Sumi M. Ultrasonography as an additional item in the American College of Rheumatology classification of Sjögren's syndrome. Rheumatology doi: 10.1093: June 6, 2014. Carotti M, Ciapetti A. Ultrasonography of the salivary glands: the role of grey-scale and colour/power Doppler. Clin Exp Rheumatol 2014; 32 (Suppl. 80): S61-S70. Theander E, Mandl T. Primary Sjögren's Syndrome: Diagnosticand Prognostic Value of Salivary Gland Ultrasonography Using a Simplified Scoring System. Arthritis Care & Research Vol. 66, No. 7, July 2014, pp 1102–1107. Disclosure of Interest: None declared